Bridge the gap breakthrough communication tools to transform work relationships from challenging to collaborative - Edwards, Jennifer (Business advisor); McCleary, Katie (McGraw Hill, 2022)
"Two coaches to Fortune 500 companies and social enterprises show how to use the social-psychology of human connection and curiosity to drive meaningful workplace communication and collaboration In today's increasingly polarized world, we're struggling to fully understand and respect one other. As a result, we're losing sight of the importance of building and maintaining professional relationships; even forgetting to be curious and listen to each other. And that's bad for business. Bridge the Gap explores the intersection of how your biology and biography define, refine, and contribute to your presence and behavior in relationships where you struggle to connect. Focusing on personal responsibility and awareness, meta-cognition, and curiosity, the book provides you with a reliable and replicable framework to increase open communication and foster better relationships at work. The authors illuminate the raw power of the human brain and mind, and how they impact the way you connect, communicate, and collaborate with people. They offer a deep dive into how you can better cooperate with people at work, especially when you struggle with differences. Bridge the Gap helps you: Master your biological reactions when pressure, stress, and anxiety hijack your efforts to connect Understand how you and others can better communicate and collaborate Lead with curiosity in all your communication strategies and learn how to give authentic feedback Feel more comfortable working on diverse teams, embracing all cultural backgrounds Whether you're entry level staff or a C-Suite executive, you'll learn how to communicate clearly with a broad spectrum of people and navigate a wide range of emotions in virtually any situation. Rather than focus solely on the mechanics of "difficult" conversations, the authors illustrate how your presence, curiosity, and language can foster better interactions and outcomes with others. Filled with practical exercises, memorable analogies, and colorful stories, Bridge the Gap provides everything you need to build solid workplace relationships in nearly any situation"--Provided by publisher.